KALIGRAFI AL-QURAN DI DESA BOROBUDUR: KAJIAN LIVING QURAN - Maryono . (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2017)
The author seeks to understand as well as analyze based on a survey from the field about the knowledge of the calligraphy of the Qur'an which is an academic anxiety program of hadith interpretation, so that the writer tries to review it from the perspective of knowledge, aside from interest in the tradition of writing and placement. This research approach will use the phenomological approach with data collection techniques carried out by interview. The results of this study are that almost all Muslim homes in the village of Borobudur have recited the Qur'an in the form of ornaments with a variety of models and sizes that are widely felt. After the houses, mosques and contents with the holy verses of the Koran seemed to have a spiritual home that occupies always feel at home, the more they look at the decoration of calligraphy, the more intrigued the mind is to draw closer to Allah. There are several reasons why Muslims in the village of Borobudur have the calligraphy of the Qur'an, that is, getting closer to Allah, understanding of the calligraphy of the Qur'an calligraphy, as a monument and calligraphy of the Qur'an as spirit